Novel yeast Pichia kudriavzevii alleviates aflatoxins induced toxicopathology in broiler chickens through immunomodulation and antioxidant enhancement - Ashiq Ali; Aisha Khatoon; Muhammad Kashif Saleemi; Rao Zahid Abbas; Bilal Murtaza; Kaynaat Akbar; Qaisar Tanveer; Sami Ullah Khan Bahadur; Hissah Abdulrahman Alodaini; Mai Ahmad Alghamdi (Ecotoxicology and Environmental Safety)
This study aimed to investigate the potential of Pichia kudriavzevii (PK), a newly discovered yeast strain, in alleviating the deleterious effects induced by aflatoxins on broilers. Eighty one-day-old broiler chicks were divided into four groups and subjected to various combinations of aflatoxin dosages at 300 μg/kg of feed alongside PK supplementation at 1 g/kg of feed. Assessment encompassed a comprehensive array of parameters including performance metrics, hepatic and renal biomarkers, interleukin concentrations, blood cell counts, hemoglobin concentration, packed cell volume, antibody response to sheep red blood cells, lymphoproliferative response to PHA-P, phagocytic response utilizing the carbon clearance assay system, as well as evaluation of oxidants and antioxidants. Additionally, gross and microscopic lesions on liver and kidney were examined. The study highlights Pichia kudriavzevii as a promising agent for mitigating aflatoxin-induced toxicity in broiler chicks by improving antioxidant and immunomodulatory status, normalizing biomarkers, and reversing pathological alterations through multifaceted protective mechanisms.